Radiocephalic Arteriovenous Fistula Patency and Use - Patrick Heindel, MD; Peng Yu, MD, PhD; Jessica D. Feliz, MD; Dirk M. Hentschel, MD; Steven K. Burke, MD; Mohammed Al-Omran, MD, MSc; Deepak L. Bhatt, MD, MPH; Michael Belkin, MD; C. Keith Ozaki, MD; Mohamad A. Hussain, MD, PhD (Annals of Surgery Open, 2022)
Objective:. We sought to confirm and extend the understanding of clinical outcomes following creation of a common distal autogenous access, the radiocephalic arteriovenous fistula (RCAVF). Background:. Interdisciplinary guidelines recommend distal autogenous arteriovenous fistulae as the preferred hemodialysis (HD) access, yet uncertainty about durability and function present barriers to adoption. Methods:. Pooled data from the 2014-2019 multicenter randomized-controlled PATENCY-1 and PATENCY-2 trials were analyzed. New RC-AVFs were created in 914 patients, and outcomes were tracked prospectively for 3-years. Cox proportional hazards and Fine-Gray regression models were constructed to explore patient, anatomic, and procedural associations with access patency and use. Results:. Mean (SD) age was 57 (13) years; 45% were on dialysis at baseline. Kaplan-Meier estimates of 3-year primary, primary-assisted, and secondary patency were 27.6%, 56.4%, and 66.6%, respectively. Cause-specific 1-year cumulative incidence estimates of unassisted and overall RC-AVF use were 46.8% and 66.9%, respectively. Patients with larger baseline cephalic vein diameters had improved primary (per mm, hazard ratio [HR] 0.89, 95% confidence intervals 0.81–0.99), primary-assisted (HR 0.75, 0.64–0.87), and secondary (HR 0.67, 0.57–0.80) patency; and higher rates of unassisted (subdistribution hazard ratio 1.21, 95% confidence intervals 1.02–1.44) and overall RCAVF use (subdistribution hazard ratio 1.26, 1.11–1.45). Similarly, patients not requiring HD at the time of RCAVF creation had better primary, primary-assisted, and secondary patency. Successful RCAVF use occurred at increased rates when accesses were created using regional anesthesia and at higher volume centers. Conclusions:. These insights can inform patient counseling and guide shared decision-making regarding HD access options when developing an individualized end-stage kidney disease life-plan.